Comparison of ease of insertion, visibility of strings and continuation rate of post-partum intrauterine copper device insertion by long inserter versus with the help of Kelly’s forceps - Shukla, Swati; Tyagi, Mamta; Gupta, Smriti; Yadav, Lalita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of the study was to compare ease of insertion, visibility of strings and continuation rate of post-partum intrauterine copper devices (PPIUCD) insertion by long inserter versus with the help of Kelly’s forceps. Methods: 100 women were enrolled in our study which was conducted in department of obstetrics and gynecology, Subharti medical college and Chattrapati Shivaji Subharti hospital (CSSH), Meerut over a period of 2 years between November 2018 and August 2020. In study comparison was done on insertion technique of PPIUCD. Results: High fundal placement was achieved with long inserter. There was no perforation and decreased infection rate among the users with no increase in incidence of side effects and expulsion. Among 50 insertion, 1 woman (2%) had partial expulsion, 2 women (4%) had complete expulsion and 1 woman (2%) got PPIUCD removed on request. Providers reported 100% easier technique. 96% satisfaction among the users. Conclusions: The dedicated long inserter PPIUCD was found to be safe, with high acceptability among the participants and providers. Study revealed the reduced risk of infection and expulsion, providers also reported increased convenience in insertion compared to standard PPIUCD insertion techniques.